Principalsâ€™ Gender-Related Variables and Discipline in Secondary Schools in Southwest, Nigeria - Olufunke, Akomolafe, Comfort; Abimbola, Belo, Fawziyah (European Scientific Journal, ESJ, 2018)
The study examined the relationship between principalsâ€™ genderrelated variables and discipline of teachers and students. The study was a descriptive research design of the survey type. The study population comprised 80, 291 teachers in Southwest Nigeria that comprised six states. A sample of 2,040 teachers was drawn from 102 Secondary Schools in 17 local Government Areas from three States in Southwest Nigeria using proportionate random and stratified sampling techniques. Data were collected with an instrument tagged â€œGender-Related Variables and Discipline Questionnaireâ€. The instrument was subjected to face and content validity by expert in Educational management and tests, to ensure the items measure what they are supposed to measure. The reliability of the instrument was established through test-retest method which yielded a coefficient of 0.78. The hypotheses were tested with Pearsonâ€™s Product Moment Correlation and Multiple Regression Analysis at 0.05 level of significance. It was revealed from the study that there was significant relationship between principalsâ€™ gender-related variables and teachersâ€™ as well as studentsâ€™ discipline. It was also revealed from the study that courage of principals was the best predictor of teachersâ€™ discipline while principalsâ€™ toughness was the best predictor of studentsâ€™ discipline. It was concluded on the basis of the findings of this study that gender-related variables are critical variables in the discipline of both teachers and students. It was therefore recommended that principals should regularly be reminded that their ability to discipline erring teachers and students is not a function of their sex but their personal attributes. It was equally recommended that principalsâ€™ knowledge need to be updated on the need to maintain those variables such as courage, toughness and friendliness that contribute to their being effective in disciplining both teachers and students.